Relative and absolute density estimates of land planarians (Platyhelminthes, Tricladida) in urban rainforest patches - Carbayo, Fernando; Matarensi Junior, Odair; Jucá, Marília (Papéis Avulsos de Zoologia, 2016)
Land planarians (Platyhelminthes) are likely important components of the soil cryptofauna, although relevant aspects of their ecology such as their density remain largely unstudied. We investigated absolute and relative densities of flatworms in three patches of secondary Brazilian Atlantic rainforest in an urban environment. Two methods of sampling were carried out, one consisting of 90 hours of active search in delimited plots covering 6,000 m² over a year, and the other consisting of leaf litter extraction from a 60 m² soil area, totaling 480‑600 l leaf litter. We found 288 specimens of 16 species belonging to the genera Geobia, Geoplana, Issoca, Luteostriata, Obama, Paraba, Pasipha, Rhynchodemus, Xerapoa, and the exotic species Bipalium kewense and Dolichoplana striata. Specimens up to 10 mm long were mostly sampled only with the leaf litter extraction method. Absolute densities, calculated from data obtained with leaf litter extraction, ranged between 1.25 and 2.10 individuals m‑². These values are 30 to 161 times higher than relative densities, calculated from data obtained by active search. Since most common sampling method used in land planarian studies on species composition and faunal inventories is active search for a few hours in a locality, our results suggest that small species might be overlooked. It remains to be tested whether similar densities of this cryptofauna are also found in primary forests.